Biomaterials and stem cells in regenerative medicine - Ramalingam, Murugan editor 526010; Ramakrishna, Seeram editor 196389; Best, Serena editor 544561 (Boca Raton, FL : CRC Press, 2012)
Includes bibliographical references and index.